Differential reflex adaptations following sensorimotor and strength training in young elite ski jumpers and nordic combined - Taube, W.; Kurz, O.; Leukel, C.; Gollhofer, A. (4th International Congress on Science and Skiing, 2007)
INTRODUCTION: In young elite ski-jumpers and Nordic combined athletes the influence of a sensorimotor training (SMT=balance training) on strength, Jump height and spinal reflex excitability was compared with adaptations induced by strength training (ST).